Business process reengineering : A comparison between rapid re methodology and clean sheet of paper / Sa'diah Sahat and Razali Karim - Sahat, Sa'diah; Karim, Razali (2004)
In the Business Process Reengineering, the debated issues regarding the BPR implementation that is often highlighted is either using a Rapid Re Methodology that was proposed by Manganelli and Klein and Clean Sheet of Paper as advocated by Hammer and Champy. This paper looks into the similarities and differences in the two methods. Clean sheet of paper is a single visionary and rapid re methodology is a team activity. Rapid Re Methodology combines the clean sheet method to proper implementation of BPR effort.